ANALYSING THE PRE-DEFORMATION IN CASE OF SELECTIVE LASER MELTING PROCESS (Perner's Contacts, 2022)
In Selective Laser Melting technology, the deformation of a metal model depends on many parameters. A complex model geometry needs simulation software to compensate for it. In this research work, the different types of model geometries, materials (316L, Ti64), and pre-deformation processes were analyzed in a Selective Laser Melting dedicated simulation software and the real model. The result shows the geometrical difference between the standard and the pre-deformed models and the simulated results and printed parts. Due to the result, the necessity of pre-deformation, the right choice of simulation parameters, and the simulation process become more understandable and predictable in SLM technology. Of the two raw materials, in the case of titanium, higher internal stresses are generated during printing, so knowing what the deformations are is even more important than in the case of steel. An important result of the research is that it clearly demonstrates where and to what extent deformation occurs in the case of post-printing operations, thus the desired geometry can better meet the requirements.